Extraction of Water Treatment Coagulant from Locally Abundant Kaolin Clays - Fidelis Chigondo; Benias Chomunorwa Nyamunda; Vuyo Bhebhe (Journal of Chemistry)
Rapid industrialisation is contributing to water pollution. There is a need to identify cheaper and efficient methods of removing contaminants as the demand for clean water rises. A study is carried out to investigate the extraction of alum from locally abundant kaolin clays using sulphuric acid. Alum is a coagulant that is used for raw water treatment. The kaolin clay and alum were characterized by Fourier transformation infrared spectroscopy (FTIR). The effects of particle size, calcination temperature, calcination time, acid-kaolin clay ratio, acid concentration, leaching temperature, and leaching time on extraction efficiency were investigated. The optimum leaching conditions for the calcined kaolin clay were found to be particle size 100 µm, acid-kaolin clay weight ratio 6 : 1, acid concentration 4 M, leaching temperature 100°C, and leaching time 90 min. Under optimised conditions, 66.95% (w/w) aluminum sulphate was extracted. The results showed that sulphuric acid could be used on a large scale to extract alum from kaolin clay. The extracted alum showed similar structural and physical characteristics compared with commercial alum. A dosage of 40 mg/L of the extracted alum showed effective coagulant properties with a great potential of treating raw water.